2011
DOI: 10.1016/j.ajpath.2011.06.038
|View full text |Cite
|
Sign up to set email alerts
|

Membrane-Bound Serine Protease Inhibitor HAI-1 Is Required for Maintenance of Intestinal Epithelial Integrity

Abstract: Hepatocyte growth factor activator inhibitor type 1 (HAI-1), encoded by the serine protease inhibitor Kunitz type 1 (SPINT1) gene, is a membrane-bound serine protease inhibitor expressed in epithelial tissues. Mutant mouse models revealed that HAI-1/SPINT1 is essential for placental labyrinth formation and is critically involved in regulating epidermal keratinization through interaction with its cognate cell surface protease, matriptase. HAI-1/SPINT1 is abundantly expressed in both human and mouse intestinal e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
47
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(48 citation statements)
references
References 41 publications
1
47
0
Order By: Relevance
“…−/− placentas display phenotypic hallmarks of Spint1 deficiency Spint1 encodes a cell membrane-associated Kunitz type 1 serine protease inhibitor (Shimomura et al, 1997) that is expressed in several epithelial cells and tissues, including the placenta, kidney and intestine (Kataoka et al, 2000;Yamauchi et al, 2004;Oberst et al, 2005;Szabo et al, 2007;Kawaguchi et al, 2011). Similar to Grhl2 −/− placentas, chorionic trophoblasts of Spint1 −/− placentas fail to establish a labyrinth, fetal vascularization is absent, and the trophoblast layer appears to be compact (Tanaka et al, 2005;Fan et al, 2007;Szabo et al, 2007).…”
Section: Grhl2mentioning
confidence: 99%
“…−/− placentas display phenotypic hallmarks of Spint1 deficiency Spint1 encodes a cell membrane-associated Kunitz type 1 serine protease inhibitor (Shimomura et al, 1997) that is expressed in several epithelial cells and tissues, including the placenta, kidney and intestine (Kataoka et al, 2000;Yamauchi et al, 2004;Oberst et al, 2005;Szabo et al, 2007;Kawaguchi et al, 2011). Similar to Grhl2 −/− placentas, chorionic trophoblasts of Spint1 −/− placentas fail to establish a labyrinth, fetal vascularization is absent, and the trophoblast layer appears to be compact (Tanaka et al, 2005;Fan et al, 2007;Szabo et al, 2007).…”
Section: Grhl2mentioning
confidence: 99%
“…Matriptase, encoded by the ST14 gene, belongs to the type II transmembrane serine protease superfamily and is expressed on the epithelial cell surface of most epithelial tissues (6). Moreover, recent studies indicate that its cognate cell surface inhibitor, hepatocyte growth factor activator inhibitor (HAI), also has crucial roles in epithelial functions (7)(8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%
“…Unlike HAI-2/ SPINT2, HAI-1/SPINT1 also has an N-terminal cysteine-rich domain and a low-density lipoprotein receptor type A-like domain (11). HAI-1/SPINT1 is expressed in most epithelial cells, with significant expression in enterocytes (8,12). HAI-1/ SPINT1 was initially discovered as an endogenous inhibitor of HGF activator, a serum-derived serine protease (13), but its membrane association may also allow it to regulate cell surface serine proteases.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…14e20 By using Spint1 mutant mouse models, we previously reported that HAI-1 is critically required in the development of the placental labyrinth 21 and normal keratinization of the skin, 22 and it may also contribute to intestinal epithelial barrier function. 23 In the absence of HAI-1, epidermis showed hyperkeratosis and decreased barrier function in mice. 22 Moreover, hair cuticle formation was severely impaired.…”
mentioning
confidence: 99%